2021
DOI: 10.1007/s11694-021-01060-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Co-60 gamma irradiation on Aspergillus flavus, Aflatoxin B1 and qualitative characteristics of pistachio nuts (Pistacia vera L.)

Abstract: In this study the effect of different doses of gamma irradiation (0, 0.5, 1, 1.5, 2, 4 and 6 kGy) on viable spore population of Aspergillus flavus, Aflatoxin B 1 (AFB 1 ) concentration and qualitative characteristics of pistachio samples were investigated. The results indicated that gamma irradiation at doses of 4 and 6 kGy reduced the viable spore population of A. flavus about 5 log. The maximum degradation of AFB 1 in pistachio samples was 73.26% and 83.36% that was observed at doses of 4 and 6 kGy, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 29 publications
6
17
1
Order By: Relevance
“…The results reported by Makari et al. (2021a) illustrated that the antioxidant activity, chlorophyll, carotenoids, and color of pistachio nuts were significantly and negatively affected at the irradiation ( 60 Co resource) dose of 6 kGy. Matrix properties also affect the irradiation efficacy.…”
Section: Degradation Of Aflatoxins By Physical Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…The results reported by Makari et al. (2021a) illustrated that the antioxidant activity, chlorophyll, carotenoids, and color of pistachio nuts were significantly and negatively affected at the irradiation ( 60 Co resource) dose of 6 kGy. Matrix properties also affect the irradiation efficacy.…”
Section: Degradation Of Aflatoxins By Physical Methodsmentioning
confidence: 95%
“…The maximum allowable dose for commercial food irradiation is regulated at 10 kGy in many countries, but its application in foods with high vitamin and lipid content should be avoided as much as possible, because these components are easily oxidized by free radicals, resulting in decline of food quality (Calado et al, 2014). The results reported by Makari et al (2021a) illustrated that the antioxidant activity, chlorophyll, carotenoids, and color of pistachio nuts were significantly and negatively affected at the irradiation ( 60 Co resource) dose of 6 kGy. Matrix properties also affect the irradiation efficacy.…”
Section: Principle and Applicationsmentioning
confidence: 99%
“…showed gamma irradiation at doses of 4 and 6 kGy led to 73.26 and 83.36 AFB1 degradation in pistachios, respectively [37]. Mehdizadeh and Amini found that pistachio AFB1 in natural uranium boilers decreased from 134.85 to 72.28 ng/g [38].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the chemical detoxification of products intended for human consumption is not permitted in the European Union (EU) [ 3 ]. Over the past decades, electromagnetic radiation has been studied as an alternative disinfection method to eliminate A. flavus and reduce or remove AFB1 contamination from foodstuffs [ 2 , 3 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Γ-treatment of maize at doses of 2, 5, and 10 kGy decreased the number of A. flavus spores under the detection limit and degraded AFB1 levels by 46% and 68.9%, and AFB2 levels by 97.6% and 94% at doses of 2 and 5 kGy, respectively [ 11 ]. The number of A. flavus spores was reduced under the investigation limit, and AFB1 levels were diminished to 73.26% and 83.36% at γ-treatment doses of 4 and 6 kGy in pistachios [ 6 ]. Jalili et al (2012) [ 8 ] reported that γ-treatment at a dose of 6 kGy of contaminated red chilies showed an 86% to 98% decrease in the AFB1 concentration and a reduction in the colony count of A. falvus .…”
Section: Introductionmentioning
confidence: 99%